2012
DOI: 10.1117/12.920397
|View full text |Cite
|
Sign up to set email alerts
|

Classification of antibiotics by neural network analysis of optical resonance data of whispering gallery modes in dielectric microspheres

Abstract: A novel emerging technique for the label-free analysis of nanoparticles and biomolecules in liquid fluids using optical micro cavity resonance of whispering-gallery-type modes is being developed.A scheme based on polymer microspheres fixed by adhesive on the evanescence wave coupling element has been used. We demonstrated that the only spectral shift can't be used for identification of biological agents by developed approach. So neural network classifier for biological agents and micro/nano particles classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Introducing controlled amount of nano particles (50 nm in diameter glass gel solution) into microsphere surrounding was accompanied also by correlative resonance shift. The most attention was concentrated on development of a technique for recognition and identification of nanoparticles and biomolecules in liquid fluids [8][9][10][11][12]. We demonstrated that the only spectral shift is not sufficient for identification of biological agents by developed approach.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Introducing controlled amount of nano particles (50 nm in diameter glass gel solution) into microsphere surrounding was accompanied also by correlative resonance shift. The most attention was concentrated on development of a technique for recognition and identification of nanoparticles and biomolecules in liquid fluids [8][9][10][11][12]. We demonstrated that the only spectral shift is not sufficient for identification of biological agents by developed approach.…”
mentioning
confidence: 98%
“…Several schemes of experimental realization of the method have been tested [13][14][15][16]. The most promising looks a scheme based on polymer microspheres fixed by adhesive on the evanescence wave coupling element [12]. The sensitivity of the developed scheme has been tested by monitoring the whispering gallery mode spectral shift.…”
mentioning
confidence: 99%
See 3 more Smart Citations